Towards better public transport services: Understanding service quality attributes of public transport in states of developing countries - Rosli, Anita; Latip, Malisah; Alwie, Aryaty; Adam Assim, Mohamad Ibrani Shahrimin (Conscientia Beam, 2024)
This research investigates the service quality attributes of PT and the influence of the attributes on users’ satisfaction. Improving public transport (PT) facilities such as road networks and connectivity systems must align with service quality aspects. This research investigates the service quality attributes of PT and the influence of the attributes on users’ satisfaction. A survey was conducted to examine users’ perceptions of the service quality of PT in Sarawak, Malaysia. Service quality indicators have been chosen based on service quality attributes in previous research and analyzed using factor analysis (FA) to group the indicators into service quality attributes. Conformity Factor Analysis (CFA) was used to determine which attributes could significantly impact users’ satisfaction. Based on the survey results, the service quality of PT services in Sarawak is average, as most of the mean scores for each indicator of service quality and user satisfaction are less than 4.0. Four service quality attributes have been obtained from FA, i.e., vehicle condition, customer service, travel experience, and accessibility. The CFA analysis and structural model results showed that the attributes of vehicle condition, customer service, and accessibility significantly positively impact users’ satisfaction. The findings in this research can be used as references for PT providers, policymakers, and the government in improving the service quality of PT in Sarawak State.